2014
DOI: 10.1111/tri.12471
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine-mediated allograft fibrosis is associated with micro-RNA-21 through AKT signaling

Abstract: SummaryCalcineurin inhibitors (CNIs) are potent immunosuppressants with associated long-term nephrotoxicity mediated by tubular epithelial cell injury and arterial vasoconstriction. We hypothesized that CNI-induced renal injury is regulated by specific microRNAs (miRNAs). In this study, we found that 46 miRNAs were significantly altered in human proximal tubular epithelial cells (HPTECs) following exposure to cyclosporine A (CsA), particularly miR-21 (5.47 AE 0.47-fold versus vehicle, P = 0.002). This increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
1
25
0
2
Order By: Relevance
“…miR-21-dependent targeting PTEN and Smad7 was also found to be responsible for the progression of renal fibrosis in human diabetic nephropathy [83]. In a model of cyclosporine A- (CsA-) induced renal injury, downregulation of Smad7 and increase in TGF- β 1 were independent of miR-21, but miR-21 mediated CsA nephrotoxicity via PTEN/Akt signaling pathway [84]. In patients with IgA nephropathy (IgAN) miR-21 was upregulated in both glomerular and tubular-interstitial tissues.…”
Section: Mir-21 In Renal Fibrosis and Inflammationmentioning
confidence: 99%
“…miR-21-dependent targeting PTEN and Smad7 was also found to be responsible for the progression of renal fibrosis in human diabetic nephropathy [83]. In a model of cyclosporine A- (CsA-) induced renal injury, downregulation of Smad7 and increase in TGF- β 1 were independent of miR-21, but miR-21 mediated CsA nephrotoxicity via PTEN/Akt signaling pathway [84]. In patients with IgA nephropathy (IgAN) miR-21 was upregulated in both glomerular and tubular-interstitial tissues.…”
Section: Mir-21 In Renal Fibrosis and Inflammationmentioning
confidence: 99%
“…For example, increased expression of miR-21 is associated with kidney fibrosis [1113]. MiR-21 also has been proven to be related to the rate of kidney function decline [14] and specificly associated with cyclosporine-mediated allograft fibrosis [15] which is a hallmark of the end-stage renal disease. Also, several microRNAs, such as miR-130, miR-192 and miR-200, have been reported to have a regulatory role in kidney diseases [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…This effect appears to be related to TLR4 downregulation by the induction of an miR, Let-7i, due to the presence of CsA. Several studies already showed that CsA can specifically induce miRs in different cell types, such as cardiomyocytes, glioma cells, and renal tubular epithelial cells [34][35][36][37]. CsA binds to cyclophilin and the cyclophilin-CsA complex will then bind to calcineurin, a protein phosphatase 2B, PP2B, and inhibit IL-2 synthesis, and thereby T-cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that Let-7 family members can modulate TLR4 signaling. Let-7i regulates TLR4 expression in cholangiocytes and contributes to epithelial immune responses against C. parvum infection [34]. Another study showed that the expression of Let-7i is associated with the TLR4 signal in coronary artery disease, and statins downregulate the signal via Let-7i expression in these patients [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation